Expression of Key Structural Genes of the Phenylpropanoid Pathway Associated with Catechin Epimerization in Tea Cultivars - Chen, Changsong; Wei, Kang; Wang, Liyuan; Ruan, Li; Li, Hailin; Zhou, Xiaogui; Lin, Zhenghe; Shan, Ruiyang; Cheng, Hao (Frontiers in Plant Science, 2017)
Catechin epimerization is an important factor affecting tea catechin compositions and thereby tea quality. However, a lack of tea germplasms with high non-epicatechins limits relative research. Here, a tea cultivar Y510 with high non-epicatechins was firstly reported and used for catechin and RNA-Seq analysis. Results showed that the (-)-gallocatechin gallate (GCG) and (+)-catechin (C) contents in Y510 were at least 136 and 6 times higher than those in Fudingdabaicha and 0306I, but the epicatechins (-)-epigallocatechin (EGC) and (-)-epicatechin (EC) were significantly lower. Eleven unigenes potentially involved in catechin epimerization were identified by RNA-Seq analysis. Based on a combination of catechin and gene expression analysis, it was hypothesized that two anthocyanidin reductase genes (CsANR1, CsANR2) and an anthocyanidin synthase gene (CsANS) are the key genes affecting catechin epimerization in tea. Non-epicatechin formations were hypothesized to be mainly influenced by the expression ratio of CsANR2 to CsANR1 and the expression of CsANS. Overexpression of CsANS in an Arabidopsis mutant tds4-2 led to a significant increase of EC accumulation in seeds, revealing CsANS is important for catechin epimerization. These results shed new light on breeding tea cultivars with special catechin compositions.